Media Massa dan Proses Konstruksi Realitas dalam Kajian Teori Sistem dan Differensiasi - Tommy Satriadi Nur Arifin (MUKASI: Jurnal Ilmu Komunikasi, 2023)
The mass media itself is referred to as "media" because of its nature as a medium / intermediary. For the discipline of Communication Science, the media (as a medium) is one of the factors forming the communication process. Whereas mass media, in general knowledge is more defined in institutions / organizations / media companies that produce information in the form of commodities traded, called mass media because the process seeks to direct the results of its production to the widest possible audience. Reality construction is the process by which mass media create information products before they are accepted by the public. Construction of reality is more defined as an effort to compile the reality of one or a number of events that were originally fragmented (random) to be systematic to form a meaningful story or discourse. This article attempts to read the process of constructing reality with the perspective of System Theory and Differentiation from Niklas Luhmann. Luhmann sees through these two perspectives that people get reality from the mass media as the second form of reality that occurs, because the first reality obtained by the mass media experiences the construction of reality when it enters the mass media area. The basis for the construction of reality in the mass media is the existence of self-references and other references present in the mass media system. The mass media system distinguishes self-references and other references in themselves in the form of the construction of reality or the results of information distributed to the public.